The declining talent pool of government. - Dewan, T; Myatt, D (Wiley-Blackwell, 2010)
We consider a government for which success requires high performance by talented ministers. A leader provides incentives to her ministers by firing those who fail. However, the consequent turnover drains a finite talent pool of potential appointees. The severity of the optimal firing rule and ministerial performances decline over time: the lifetime of an effective government is limited. We relate this lifetime to various factors, including external shocks, the replenishment of the talent pool, and the leader's reputation. Some results are surprising: an increase in the stability of government and the exogenous imposition of stricter performance standards can both shorten the era of effective government, and an increase in the replenishment of the talent pool can reduce incumbent ministers' performance.